Efektivitas kotoran ternak sebagai aktivator pupuk organik dalam mereduksi limbah blotong tebu - Al-Irsyad, Muhammad; Kurniawan, Agung; Aini, Rosiana Fadilatul; Adji, Lanang Laksita; Lumitasari, Sherly Dia; Aini, Febrianty Quratul; Rahmadita, Fariza Eky Putri; Ramadhan, Alfaka (Holistik Jurnal Kesehatan, 2025)
Background: Livestock farming in Malang Raya has been carried out in line with the increasing public awareness of the nutritional value of animal protein. Not infrequently, livestock commodities are sold to other cities, ensuring a consistent abundance of livestock farms in Malang. However, livestock farming generates various types of waste, leading to concerns and potential pollution in various sectors. Therefore, the utilization of livestock waste, such as manure and sugarcane bagasse, as organic fertilizer can have a positive impact on the environment. Purpose: To determine the effectiveness of livestock manure as an organic fertilizer activator in reducing sugarcane bagasse waste. Methods: A quantitative experimental research design using a posttest-only control group design through laboratory testing of fertilizer quality. Organic fertilizer production was carried out using the takakura composting method with aeration in fertilizer piles. Results: The mixture of sugarcane bagasse waste and manure as a bioactivator was effective in meeting the physical characteristics of organic fertilizer. Furthermore, the mixture of sugarcane bagasse waste and manure as a bioactivator met the nutrient quality of solid organic fertilizer in all parameters. The most effective composition of the mixture of sugarcane bagasse waste and manure activators in producing high-quality fertilizer was a mixture of 15% cow manure, 15% chicken manure, 60% sugarcane bagasse waste, and 10% finished compost. Conclusion: A mixture of sugarcane bagasse waste with cow and chicken manure as a bioactivator has proven to be effective as an organic fertilizer with the mixture composition being the most effective.